Organizational changes in emerging economies: drivers and consequences - Zhou, Kevin Zheng; Tse, David K; Li, Julie Juan (Journal of International Business Studies, 2006)
Organizational change in emerging economies, although difficult, is inevitable. The authors study the drivers and consequences of organizational changes in an emerging economy, China. The results of a firm-level survey show that organizational changes in technical vs administrative areas are differentially driven by firms' motivation to change (past performance), opportunity to change (firm location and market orientation), and capability to change (firm ownership, managers' change attitude, and leader charisma). Furthermore, technical and administrative changes affect firm performance through distinct paths. Technical changes have a direct, positive impact on performance, whereas administrative changes enhance firm performance indirectly through technical changes, and the effect of administrative changes on performance is strengthened by the presence of a participative culture.